2021
DOI: 10.3389/fimmu.2021.735576
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Lambda Signaling in Macrophages Is Necessary for the Antiviral Response to Influenza

Abstract: Interferon lambda (IFNλ) signaling is a promising therapeutic target against viral infection in murine models, yet little is known about its molecular regulation and its cognate receptor, interferon lambda receptor 1 (IFNLR1) in human lung. We hypothesized that the IFNλ signaling axis was active in human lung macrophages. In human alveolar macrophages (HAMs), we observed increased IFNLR1 expression and robust increase in interferon-stimulated gene (ISG) expression in response to IFNλ ligand. While human monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…In humans, the IFNλ‐IFNLR1 signaling axis is crucial in inhibiting influenza infection 24,25 . While there is currently no clinically approved IFNλ drug, clinical trial results demonstrate its efficacy in reducing the pathogenesis or viral load caused by respiratory infections, including COVID‐19 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the IFNλ‐IFNLR1 signaling axis is crucial in inhibiting influenza infection 24,25 . While there is currently no clinically approved IFNλ drug, clinical trial results demonstrate its efficacy in reducing the pathogenesis or viral load caused by respiratory infections, including COVID‐19 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“… 43 Alternatively, monocytes may not respond to the dominant IFN (type III, IFN-λ) at epithelial barrier surfaces 44 46 because they lack expression of the IFNLR1 subunit. 47 49 Differences in permissiveness to CHIKV infection of monocytes from blood, DLN, and tissue also could be due to their transcriptional or programmatic differences. 50 It will be important to continue to characterize monocyte subsets and their functions in diverse inflammatory settings, including during virus infections such as CHIKV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that early IFN-λ treatment in mice during influenza virus infection offers significant antiviral protection without the proinflammatory responses associated with Type 1 interferons ( 6 , 25 ). Although we have previously demonstrated the presence of the IFN-λ–IFNLR1 signaling axis in human lung macrophages and its role in combating influenza infection, the expression, signaling, and molecular regulation of IFNLR1 in human bronchial epithelial cells has not been fully elucidated ( 26 ).…”
Section: Discussionmentioning
confidence: 99%